ANALISIS FAKTOR AUDIT MUTU INTERNAL ISO 9001:2015 - Fransisca, Septiani; Aliya, Sabeli (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
Many companies have implemented ISO 9001: 2015 but no research has focused on the factors that make up the internal audit quality variables. This research took place at the Rumah Sakit Umum Daerah of Kayu Agung of Ogan Komering Ilir Regency. This research uses quantitative descriptive method. The population is stakeholders related to the entity, the sample using cluster sampling and simple random sampling. The data used are primary data derived from the dispersed questionnaire. The distribution of questionnaire was conducted in 2018. The technique of data analysis using normality test and factor analysis. In analyzing the researchers using KMO and Bartletts Test, Communalities, Anti-Image Matrices, The Scree Plot, and Component Matrix. Factors tested consisted of customer focus, leadership, HR involvement, process approach, continuous improvement, fact-based decision making, and stakeholder relationships. The results showed all the factors have a very good correlation of above 0.870 to the variables studied.